Testicular Adrenal Rest Tumors in Congenital Adrenal Hyperplasia: Study of a Cohort of Patients from a Single Italian Center - Rita Ortolano; Alessandra Cassio; Randa S. Alqaisi; Egidio Candela; Valeria Di Natale; Valentina Assirelli; Luca Bernardini; Elisa Bortolamedi; Erika Cantarelli; Beniamino Corcioni; Matteo Renzulli; Antonio Balsamo; et al. (MDPI AG, 2023)
Testicular adrenal rest tumors (TARTs) are a common complication in male patients with congenital adrenal hyperplasia (CAH). The aim of our cross-sectional cohort study is to estimate the frequency of TARTs with the correlation of genotype and disease control on tumor development. Thirty-five male patients, aged 14-26 years, were included in the study, all followed by the same center of pediatric endocrinology in Bologna. We studied genotypes, hormonal profiles at different time intervals and testicular ultrasound. A logistic regression model with multivariant analysis was developed for the statistical analysis. TARTs were detected in 31.4% of the cases, 90.9% of them had a classic form with salt wasting, while 9.1% had a non-classic form. Additionally, a significant correlation between the incidence of TARTs and severity of genotype was detected. Patients with TARTs had markedly worse metabolic control on average (p = 0.027), reflected by high ACTH, 17OH progesterone, and overall delta4-androstenedione. In conclusion, a screening tool is mandatory, especially (but not exclusively) in patients with the most severe forms of CAH and poor endocrine control of the disease.